Full reserve system and the Maqasid Shariah / Zuriyati Ahmad, Abdul Ghafar Ismail - Ismail, Abdul Ghafar (Faculty of Business and Management, Universiti Teknologi MARA Selangor, 2017)
The essence of the monetary system today is in using the fractional reserve banking system. Nonetheless, this system is not free of critics such as the fraud of making loans and creating deposits out of nothing which are argued to create distortion to the economy. Since 1930s, many economic scholars have debated the use of full reserve system as an alternative tool of monetary system.Islamic scholars also argue and reject the working of fractional reserve banking system and propose the idea of full reserve system. From the view of Islamic scholars, the full reserve system should be applied to avoid the riba’ in the monetary system. Hence, this study tries to assess whether the use of full reserve system can attain the Maqasid Shariah to support the alternative banking system. Using the argument on fractional reserve system, discussion on the concept of full reserve system, analysis of the impacts of full reserve system and the support from Quran and Hadith, this study concludes that the injustice and riba’ can be avoided under thefull reserve system, hence,attaining the Maqasid Shariah.